TRAFFIC ACCIDENT PROBLEM AREA RANTAU BERANGIN- UJUNG BATU ROKAN HULU DISTRICT, RIAU PROVINCE - Abdul Kudus Zaini; Ulfajri Fauzi (JURAL RISET RUMPUN ILMU TEKNIK, 2022)
A traffic accident is an event that occurs in a traffic flow due to an error in the traffic shaping system that involves humans as drivers, vehicles, roads, and the surrounding environment. In this study, the road that was studied was Rantau Berangin - Ujung Batu which was a class III collector road with a length of ± 66.5 km. This study aims to determine the level of traffic accidents in the area to obtain the Accident Rate value on the Black Spot and Black site . The method in this research is a qualitative method to get the value of the Black Spot and Black Site based on the accident rate. The data used are primary and secondary data obtained from the Kampar Police from 2014 - 2018, as well as those related to traffic accidents. The results of analysis of the received data show that the rate of traffic accidents on roads Rantau Berangin - Ujung Batu is relatively high with 24 scenes of the accident, which roads rantau Berangin - Silam be the point most vulnerable areas of traffic accidents with Accident Rate of the Black Spot by 9,767 and the Accident Rate of the Black Site is 1,205. Meanwhile, the factors that cause traffic accidents on the Rantau Berangin - Ujung Batu road section are dominated by human factors themselves, such as driving at high speed in crowds and using other drivers' lanes.